4-(2-{[4-Amino-6-(4-nitrobenzyl)-5-oxo-4,5-dihydro-1,2,4-triazin-3-yl]sulfanyl}acetyl)-3-phenylsydnone - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the crystal, C(20)H(15)N(7)O(6)S, the dihedral angle between the oxadiazole and triazine rings is 86.94 (7)°. The oxadiazole ring makes a dihedral angle of 52.96 (8)° with the phenyl ring, while the triazine ring makes a dihedral angle of 82.08 (7)° with the benzene ring. In the structure, molecules are linked by a pair of N—H⋯O hydrogen bonds, forming an inversion dimer. The dimers are further stacked along the a axis via N—H⋯N hydrogen bonds. Weak intermolecular C—H⋯O interactions are also observed.